Analisis Faktor-Faktor yang Mempengaruhi Niat Perilaku Penggunaan Layanan Mobile Banking - Lutfi Alviandi; Rojuaniah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The COVID-19 pandemic that hit Indonesia in the first quarter of 2020 has pushed the banking industry to experience change and development through technology-based innovation. With information technology, banks are able to provide easy transaction services and access to information, as well as connecting the bank with its customers through the use of the internet, one of which is mobile banking. Behavioral intention to use can describe how much a customer wants to use mobile banking services, while use behavior is the intensity and/or frequency of users in using information technology. The aim of this research is to determine the behavioral intention to use mobile services. banking at one of the Government Banks of the Republic of Indonesia. This research uses a quantitative method with data collection distributed through a questionnaire in the form of a Google form. This research sample consists of 180 customers who have used the service for more than 1 (one) month. This research data was analyzed using SEM. The research results show that performance expectancy, effort expectancy, social influence, habit, and timeliness have a significant positive effect on behavioral intention to use. Apart from that, perceived risk has a significant negative effect on behavioral intention to use. Behavior intention to use has a significant positive effect on use behavior. Meanwhile, facilitating conditions, hedonic motivation, and price value have no effect on behavioral intention to use.